CONTROL OF DAMPING-OFF OF SUGARBEET BY SEED TREATMENT WITH METALAXYL - A. N. MUKHOPADHYAY, INDU S. SAWANT AND (Indian Phytopathology, 2002)
Metalaxyl was highly inhibitory to P. aphanidermatum with (:050 at 2.9 ppm. Combination products, viz. ridomil Mz and metalaxyl + zineb were significantly less inhibitory than metalaxyl alone. Seed treatment with 1000 ppm metalaxyl gave complete protection against damping-off for the entire 28 days susceptible period. After seed treatment, approximately 1/3 of the applied metalaxyl was taken up by the seeds within 24 h. Most of the fungicide accummulated in the leaves, especially leaf tips. Metalaxyl could be detected in the roots and stem of sugar beet seedlings till 24 days and in the leaves till 44 days after seed treatment.